1996
DOI: 10.1182/blood.v87.9.3963.bloodjournal8793963
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of mafosfamide-resistant pre-colony-forming units in allogeneic bone marrow transplantation: relationship with rate of engraftment and evidence for long-lasting reduction in stem cell numbers

Abstract: Current assays of human committed-stem cells are of limited value in predicting the rate of engraftment or in assessing the integrity of the stem cell pool after allogeneic bone marrow (BM) transplantation (BMT). We have used a limiting dilution assay of mafosfamide-resistant progenitors (pre-colony-forming units [CFU]), which are ancestral to committed progenitors such as CFU-granulocyte-macrophage (GM) to analyze the kinetics of myeloid engraftment after BMT and to assess the size of the stem cell pool at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
6
11
0
Order By: Relevance
“…We have previously shown that during G-CSF-enhanced recovery PB is enriched with the more immature CD34 / Thy1 progenitor cell subset (Haas et al, 1995a), but following PBSC-supported high-dose therapy the proportion of this subpopulation and of CD34 /DR ÿ cells is significantly reduced in BM, when compared with pre-mobilizationvalues. This finding is similar to the results of Kirkland et al (1996) who showed a reduced number of mafosfamide-resistant primitive progenitor cells after BMT. In contrast, the number of CD34 /CD33 cells post-transplantation was increased.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We have previously shown that during G-CSF-enhanced recovery PB is enriched with the more immature CD34 / Thy1 progenitor cell subset (Haas et al, 1995a), but following PBSC-supported high-dose therapy the proportion of this subpopulation and of CD34 /DR ÿ cells is significantly reduced in BM, when compared with pre-mobilizationvalues. This finding is similar to the results of Kirkland et al (1996) who showed a reduced number of mafosfamide-resistant primitive progenitor cells after BMT. In contrast, the number of CD34 /CD33 cells post-transplantation was increased.…”
Section: Discussionsupporting
confidence: 91%
“…We report on a reduction in the proportion of CD34 cells and colony-forming cells in BM and PB in patients after PBSCsupported high-dose therapy. A similar finding was made in patients following autologous or allogeneic bone marrow tranplantation (Barrett & Adams, 1981;Li et al, 1985;Ma et al, 1987;Vellenga et al, 1987;Messner et al, 1987;Mauch & Hellman, 1989;Domenech et al, 1995;Kirkland et al, 1996). The patients in this study were evaluated before PBSC mobilization and after a minimum observation period of 6 months post-transplantation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition to its direct toxic effect, chemotherapy may induce premature ageing of the stem cell population by the serial cycles of repopulation it induces in vivo. This hypothesis is supported by the long-lasting haemopoietic defect observed after repopulation following ABMT (Domenech et al, 1995), allogeneic BMT (Kirkland et al, 1996) and peripheral stem cell transplantation (Voso et al, 1996). A third possibility is that acute myeloid leukaemia is responsible for a long-lasting haemopoietic inhibition (Van Bekkum et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The synergy between SCF and G-CSF in mobilization could be related to the lower expression of c-kit (reviewed in Roberts et al, 1999). By comparison, the lack of significant synergism with the combination of IL-3 and GM-CSF is understandable because both cytokines share signalling through a common receptor b-chain (Le Âvesque et al, 1995).…”
Section: Cd34mentioning
confidence: 99%